Brand narratives and economic identity: a semiotic analysis of Indonesian startup branding language - Ahmad Qosim (CV Narasi Khatulistiwa Indonesia, 2026)
Background: The growth of Indonesia’s digital economy, valued at USD 82 billion in 2023, underscores the importance of understanding how startups construct brand identity through semiotic, narrative, and linguistic strategies. Objective: This study aims to examine how Indonesian startups employ logos, slogans, and storytelling to build economic identities that resonate with local cultural values while projecting global modernity. Method: Using a qualitative descriptive design, this research analyzed multimodal data from official websites, mobile applications, and social media campaigns of leading startups, applying semiotic analysis, narrative discourse analysis, and a brand linguistics framework. Results: The findings reveal that visual symbols such as logos and color schemes function not only as identifiers but also as cultural myths naturalizing inclusivity and progress; narrative storytelling consistently follows a problem–solution–transformation structure that situates startups as social enablers; and linguistic strategies employ hybridity, empowerment discourse, and metaphor to construct economic subject positions. Together, these results demonstrate that branding operates as both communication and ideology, embedding startups within national development narratives while simultaneously aligning with global capitalist aesthetics. Implication: The implications suggest that brand language in emerging markets is a powerful site of cultural negotiation, offering insights for scholars of discourse and practitioners of digital branding alike. Novelty: This study reveals how Indonesian startups strategically mobilize semiotic, narrative, and linguistic resources to construct hybrid brand identities that negotiate local cultural values while projecting global economic modernity.